Excellence is expected : quality monitoring and improvement in veterinary medicine - Rooke, Freya (2023)
Introduction: There is significant need for further theoretical and practical development in the field of quality improvement (QI) for use in veterinary medicine. The central aim of this thesis was to investigate the potential benefits and application of QI methods in UK veterinary practice, including how these methods could uphold and improve the quality of care delivered, and any barriers that may prevent the use of QI in practice.